Average dynamics of a driven set of globally coupled excitable units - Alonso, Leandro Martín (2011)
We investigate the behavior of the order parameter describing the collective dynamics of a large set of driven, globally coupled excitable units. We derive conditions on the parameters of the system that allow to bound the degree of synchrony of its solutions. We describe a regime where time dependent nonsynchronous dynamics occurs and, yet, the average activity displays low dimensional, temporally complex behavior. © 2011 American Institute of Physics.